IMPLEMENTASI KEBIJAKAN PELATIHAN DALAM UPAYA MENINGKATKAN KINERJA KARYAWAN PADA HUMAN RESOURCES DEPARTMENT DI THE APURVA KEMPINSKI BALI - Nyoman Omy Trisna Dewi; I Ketut Pasek; Kasiani Kasiani; I Made Sarjana; Cokorda Gede Putra Yudistira; AA Ayu Mirah Kencanawati; Lily Marheni (Media Bina Ilmiah, 2023)
The purpose of this research is to determine the implementation of training policies in an effort to improve employee performance in the human resources department at The Apurva Kempinski Bali, along with the obstacles that occur. This research uses descriptive qualitative method with technique of collecting data such as observation, interviews, and documentation. The Apurva Kempinski Bali focuses on the training policy program as one of the right policies to instill a work spirit that is in line with company values. Training is not only given to new employees as an orientation step, but also given to old employees as long as there is a gap between the abilities or expertise of the employees concerned by the needs of the organization. The process of implementation training policies in an effort to improve employee performance starts from analyzing training needs and, this becomes the basis for determining the material and duration of time to be provided. Then determine the training objectives, followed by determining the training methods, namely Role Playing, Case Study Method, and Job Rotation. After determine the methods, the implementation of the training policy is in accordance with the predetermined schedule, and the final process is the evaluating of the training policy program. Obstacles in implementing training policies in an effort to improve employee performance are the absence of a Training and Development Manager who focuses on supervising, coaching and reporting on any developments that occur during the implementation of the training policy program, and limited funds provided to conduct training.